Aplikasi Pengenalan Nama Benda dalam Bahasa Jepang dengan Metode GDLC Berbasis Android: Array - Kurniawan, Ryandra Radifa; Harliana, Putri; -, Khairunnisa (Jurnal Ilmu Komputer dan Sistem Komputer Terapan (JIKSTRA), 2022)
The development of information and communication technology in the field of education can turn abstract learning into concrete through android-based learning media. The development of learning media requires software development methods, one of which is the Game Development Life Cycle (GDLC) method. Game Development Life Cycle (GDLC) is a method that handles game development from start to finish. This educational game contains elements of text, images, audio and 3D animation that are designed as attractive as possible to increase the attraction for beginners in learning Japanese. In making this educational game using Adobe Photoshop and Unity 3D software. The purpose of this study is to help beginners learn to know more about recognizing object names in Japanese with an attractive appearance and provide a different atmosphere and learning method.